Selling War : the Role of the Mass Media in Hostile Conflicts from World War I to the ""War on Terror"" - Seethaler, Josef (European Communication Research and Education Association series., 2013)
This book is the first collection of essays to explore the changing relationships between war, media, and the public from a multidisciplinary perspective and over an extended historical period. It is also the first textbook for students in this field, discussing a wide range of theoretical concepts and methodological tools for analyzing the nature of these relationships. The book starts with a thorough overview by Philip Seib of war, the media and the public sphere. His chapter explores how the perception of war in the public sphere is influenced by the media and, more precisely, how the news.